2020
DOI: 10.3389/fonc.2020.01209
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence (AI) Assisted CT/MRI Image Fusion Technique in Preoperative Evaluation of a Pelvic Bone Osteosarcoma

Abstract: Surgeries of pelvic bone tumors are very challenging due to the complexity of anatomical structures and the irregular bone shape. CT and MRI are used in clinic for tumor evaluation, each with its own advantages and shortcomings. Combining the data of both CT and MRI images would take advantage of the merits of both images and provide better model for preoperative evaluation. We utilized an artificial intelligence (AI)-assisted CT/MRI image fusion technique and built a personalized 3-D model for preoperative tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…This increases the difficulty of diagnosis in children with osteosarcoma. In [ 22 ], image fusion technique based on advanced AI classifiers is proposed to diagnose osteosarcoma using the data of both CT and MRI images.…”
Section: Related Workmentioning
confidence: 99%
“…This increases the difficulty of diagnosis in children with osteosarcoma. In [ 22 ], image fusion technique based on advanced AI classifiers is proposed to diagnose osteosarcoma using the data of both CT and MRI images.…”
Section: Related Workmentioning
confidence: 99%
“…For all the cases included in this study, enhanced CT and MRI data were obtained to construct the 3D fusion image model as previously reported 23 . The slice thickness of MRI was less than 2 mm, normally 1 mm based on the machine or scan methods used.…”
Section: Methodsmentioning
confidence: 99%
“…Pilot attempts have been utilized in other organs using CT and MRI fusion techniques in guiding clinical practice 20–22 . We previously reported a successful case using the CT/MRI fusion 3D model to evaluate and plan the surgery of a pelvic osteosarcoma patient 23 . No study has been reported to compare the accuracy of the CT/MRI fusion model with CT only model.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works for medical imaging fusion using deeplearning techniques have been introduced in [9], [11], [13], [23], [31], [39], [41], [69], [85]- [88].…”
Section: Introductionmentioning
confidence: 99%